Design and analysis of a continuous optoelectronic pulse wave velocity blood pressure sensor with multiple-subject controlled experiments - Erkurşun, Burcu; Uçar, Atila; Tekin, Ahmet (Sensors and actuators. A. Physical., 2022)
The main purpose of this study is to perform the pulse wave velocity (PWV) measurements with a new noninvasive optoelectronic continuous-time wearable sensor design and to analyze the quantitative relation between the reference blood pressure (BP) measurement. PWV was measured at baseline 32 normotensive volunteers, including 15 females and 17 males aged between 23 and 41 years old. The day before the measurements, the volunteers were not allowed to drink alcohol, stay up late or use any medicine that would affect BP. Repeated BP measurements were performed with an average follow-up system at certain times of the day. Results: Equivalent constituents were established after questioning age, height, weight, physical activity levels in daily life, genetic predisposition for blood pressure and diabetic from all volunteers participating in the measurements. Systolic BP (SBP), diastolic BP (DBP), heart rate (HR), pulse pressure (PP), mean arterial pressure (MAP), distance between brachial to radial artery (D), pulse transit time between brachial to radial artery (brPTT) and PWV measurements were all collected to correlate results with the introduced sensor’s readings. Following the experimental results, a linear link was found between SBP and PWV when the two groups separated by gender related were examined and the correlation coefficients between them were r: 0.9915 in females and r: 0.9845 in males Measurements taken with the new non-invasive low-power continuous-time sensor design show that the PWV may in the near future be used as a screening tool to identify continuous SBP values in clinical practice. The new non-invasive design suggests that SBP has the strongest correlation with PWV among a variety of BP parameters. [Display omitted] •Non-invasive continuous monitoring of blood pressure may improve the quality of life for patients.•Pulse wave velocity measurement (PWV) is one of the promising methods to measure blood pressure.•A simple wearable sensor has proven a distinguishable correlation between PWV readings and corresponding blood pressure.•A multi-subject human experiments from a variety of groups have suggested that PWV can be a candidate for blood pressure sensors.